Penerapan Good Corporate Governance dalam Meningkatkan Efisiensi Pengelolaan Badan Usaha Milik Negara - Linda Arisanty Razak; Wa Ode Rayyani; Salwa Khaerunniza (Perspektif Akuntansi, 2023)
This study aims to examine the effect of Good Corporate Governance as measured by the board of directors, independent board of commissioners and public ownership on the management efficiency of State- Owned Enterprises. The type of research used is a type of quantitative research. This study uses secondary data obtained from the annual financial reports of state-owned enterprises. The population in this study is State- Owned Enterprises from 2017-2022. The method used in sampling is purposive sampling method so that a sample of 11 companies is obtained. The analysis technique used in this research is panel data regression analysis with the selected regression model, namely the Random Effect Model (REM) using the Eviews 12 program. The results of this study indicate that the independent board of directors and board of commissioners variables have no effect on the management efficiency of State-Owned Enterprises. Meanwhile, the public ownership variable has a positive effect on the management efficiency of State-Owned Enterprises.